Administrative Discretion in Indonesia & Netherland Administrative Court: Authorities and Regulations - Suparto, Suparto; Adinda, Fadhel Arjuna; Esanov, Azamat Esirgapovich; Normurotovna, Zamira Esanova (Journal of Human Rights, Culture and Legal System, 2024)
Discretion is used by state administrators (executives) to resolve complex government situations while still paying attention to the public interest. The practice of discretion still causes problems and debates. This research seeks to examine issues in discretionary authority and its testing. This research is normative juridical research using primary and secondary legal materials. The research approach was carried out using a statutory and conceptual approach. An analysis of the regulations and practices of discretionary testing at SAC was also added to complete the arguments that will be compared between Indonesia and the Netherlands. The findings of this research show that regulations in Indonesia contain provisions governing the limits and scope of discretion as a reference for the government in issuing discretion, as well as instructions for testing discretion at the State Administrative Court. The authority to use discretion, which has encountered problems that have arisen, includes aspects of the meaning of discretion, which also include factual actions, aspects of the regulation of discretion which are carried out in detail in the law, procedural aspects in the use of discretion which require prior permission, and aspects of the possibility of rejection of discretion by superior officials. Regarding the comparison of discretionary tests in the SAC, in Indonesia, the discretionary test is not substantially regarding discretion but instead is on the abuse of authority in exercising discretion concerning the terms and objectives of the discretion and conformity with the AUPB. Meanwhile, the SAC carries out a 'reasonableness test'—limited to whether administrative powers have been exercised fairly. Therefore, the conditions for restricting the use of discretion must be carried out strictly and need to be based on the AUPB so that discretion is issued that is not arbitrary in the public interest because discretionary authority cannot be tested in the SAC.